Optimizing the Food–Energy–Water Nexus: A Multi-Objective Spatial Configuration Framework for High-Density Communities - Jie Zheng; Hengyu Li; Lulu Sun; Mingxuan Li; Yukun Zhang (Buildings, 2025)
Global urbanization and climate change are intensifying challenges in the sustainable management of the Food–Energy–Water (FEW) system. This study introduces a multi-objective optimization framework that redefines urban spaces through a dual rooftop-ground hierarchy, interlinkage nodes for mapping material and energy flows, and the application of NSGA-II optimization to balance food production, energy output, and costs. The framework was applied to a case study area, generating non-dominated solutions with diverse resource-cost configurations. The findings revealed that optimal scenarios could meet 40.6% of local energy demands and exceed 102.9% of local grain demands, while maintaining economic viability. This approach bridges resource systems theory and spatial planning practice, providing economically viable pathways for high-density cities to transform into hybrid production-consumption spaces, effectively addressing the dual pressures of urbanization and climate change.